Kriteria Pemimpin dalam Al-Qur'an (Analisis Tafsir as Sya’rawi dalam Surah as Saff ayat 2-3 dan Surah Al Baqarah ayat 124 dalam Kitab Tafsir as Sya’rawi) - Anwar, Nafiza Fadia (Lembaga Yasin AlSys, 2023)
This study examines the filtering of leaders in the Koran (analysis of Sha'rawi's interpretation in surah As-Saff: 2-3 and Al-Baqarah: 124. This type of research belongs to a qualitative method. A qualitative research method is a research method based on a postpositive philosophy or interpretive, used to study the condition of natural objects, where the researcher is the key instrument. The results of this research are that in the Qur'an it is stated that there are four characteristics that must be fulfilled by the prophets, who are essentially the leaders of their people. First, Al-Sidq, the truth and sincerity in slavery, speaking, and carrying out tasks. Second, Al-amanah, or belief, which makes him take care of what is entrusted to him as well as possible, both from God and from the people he leads, so as to create a sense of safe for all parties. Third, Al-Fatanah, namely intelligence that gives birth to the ability to face and overcome problems that arise instantly though. Fourth, At-Tablig, which is looking for honest and responsible, or can be termed